2002
DOI: 10.1155/2002/132504
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Cell Surfaces of Estrogen Treated Breast Cancer Cells Detected by A Combined Instrument for Far‐Field and Near‐Field Microscopy

Abstract: The response of single breast cancer cells (cell line T‐47D) to 17β‐estradiol (E2) under different concentrations was studied by using an instrument that allows to combine far‐field light microscopy with high resolution scanning near‐field (AFM/SNOM) microscopy on the same cell. Different concentrations of E2 induce clearly different effects as well on cellular shape (in classical bright‐field imaging) as on surface topography (atomic force imaging) and absorbance (near‐field light transmission imaging). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first report describing the effects of 20-nm AuNPs in combination with E 2 (1×10 −9 M) on the cell surface roughness of any cell line. Perner et al (2002) demonstrated that the surfaces of ER-positive human breast cancer cells (T-47D) became increasingly jagged at physiological E 2 concentrations (5×10 −9 and 5×10 −7 M), as detected by an increase in membrane height in near-field light transmission images 68. MCF-7 cells have been reported to exhibit a more disorganized filamentous cytoskeleton structure, increased membrane roughness, decreased viscoelastic properties (elasticity and viscosity) and softer and more fluid membranes compared to benign breast cells MCF-10A 60.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report describing the effects of 20-nm AuNPs in combination with E 2 (1×10 −9 M) on the cell surface roughness of any cell line. Perner et al (2002) demonstrated that the surfaces of ER-positive human breast cancer cells (T-47D) became increasingly jagged at physiological E 2 concentrations (5×10 −9 and 5×10 −7 M), as detected by an increase in membrane height in near-field light transmission images 68. MCF-7 cells have been reported to exhibit a more disorganized filamentous cytoskeleton structure, increased membrane roughness, decreased viscoelastic properties (elasticity and viscosity) and softer and more fluid membranes compared to benign breast cells MCF-10A 60.…”
Section: Resultsmentioning
confidence: 99%
“…However, storage of samples is not discussed extensively in the literature and this is clearly important when considering the results presented here. The SNOM technique is likely to become an essential research tool in the fields of medicine and biology, indeed it has recently been applied to imaging breast cancer cells (Perner et al ., 2002) to understand the morphological effects of high dosages of 17beta‐estradiol (E‐2) using light transmission through the samples.…”
Section: Discussionmentioning
confidence: 99%
“…total internal reflection fluorescence (TIRF) microscopy (TIRFM) [118,119] or near-field scanning optical microscopy (SNOM, NSOM) [120,121], belong to the first techniques breaking the diffraction limit by novel techniques working in the optical near field of fine crystal tips probing the specimen without an microscope objective lens. Unfortunately, near-field techniques are technically restricted to the visualization of surfaces of cells, membranes or isolated organelles [122][123][124].…”
Section: Super-resolution Microscopymentioning
confidence: 99%